Pitt–Hopkins syndrome with electrical status epilepticus in slow-wave sleep: a case report - N. G. Lyukshina (Русский журнал детской неврологии, 2019)
Pitt–Hoppkins syndrome is rare genetic disorder caused by a molecular variant of TCF4 which is involved in embryologic neuronal differentiation. The syndrome is characterized by specific facial dysmorphism, phychomotor delay, autistic behavior and intellectual disability. Other associated features include ealy-onset myopia, seizures, constipation and hyperventilation-apneic spells. We introduced a clinical case of the patient with molecularly confirmed TCF4 variant and previously undescribed combination with syndrome of the electrical status epilepticus during sleep.